Report from the 24th Congress of the European Association of Urology, Stockholm, Sweden, 17-21 March 2009, dedicated to renal carcinoma - Chiara Paglino (Frontiers Media S.A., 2011)
Once again, this year's annual congress of the European Association of Urology (EAU) proved to be of great interest, not only for those more directly involved, the urologists, but also for who, like me, participated as an observer from the field of medical oncology...